Math

x+y=3
3x+2y=2

How to do this problem with substitution
I would appreciated the help.

  1. 👍 0
  2. 👎 0
  3. 👁 113
  1. you put y on one side so its x=3-y
    then substitute that into the bottom equation. so you get 3(3-y)+2y=2
    which is 9-3y+2y=2 then just solve for y.
    y=7

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra PLEASE HELP!!

    What advantages does the method of substitution have over graphing for solving systems of equations? Choose the correct answer below. A. Graphing cannot be used to solve dependent or inconsistent systems due to the nature of the

  2. Math

    1. Explain the advantages and disadvantages of both the substitution method and the elimination method for solving a system. Help please. The only reasons I can think of is because in substitution it might be more difficult cause

  3. Geometry

    Substitution Property of Equality: If a=20, then 5a= _____. The substitution rule states that If a=b then a can be substituted for b in any equation or expression. So I think that 5a=5b but the number answer is 100. Am I correct?

  4. Algebra

    Solve the system by substitution. -5x + y = -3 3x - 8y = 24 I'm not sure which equation to choose as I begin to find the y value. Some assistance would be greatly appreciated! Thank you!

  1. Algebra II

    Use synthetic substitution to find f(-3) for f(x) = 2x^3 - 6x^2 - 5x + 7. _3|2 -6 -5 7 6 36 93 ______________ 2 0 31|100 then I used direct substitution and just plugged -3 in for x and the final answer is f(-3) = 86

  2. trig

    Use substitution to determine whether the given x-value is a solution of the equation: sin x = -2sqrt3/3, x=4pi/3 A) Yes B) No C) More information is needed D) The problem is indeterminate

  3. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

  4. calculus

    We're doing indefinite integrals using the substitution rule right now in class. The problem: (integral of) (e^6x)csc(e^6x)cot(e^6x)dx I am calling 'u' my substitution variable. I feel like I've tried every possible substitution,

  1. Microeconomics

    1. The utility function is given by: U=x+y and the budget line is x+2y=100. Then the price of good x goes up to 4. Find the Hicksian substitution effect, income effect, and total change in demand for good x from the change --- Ok

  2. Calculus

    Evaluate the definite integral. dx/(x*sqrt(lnx)) from 1 to e^4 I'm having trouble figuring this out, I might be overthinking it. The way I've approached this is by using u substitution and letting u=lnx. I keep getting the wrong

  3. algebra

    i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of

  4. Pre-Calculus

    What are the vertices and co vertices of the ellipse x^2/4 + y^2/25=1 I actually have no idea how to even start to solve this problem, so any help will be appreciated. Steps on how this problem is solved are also appreciated.

You can view more similar questions or ask a new question.